Perbandingan Sistem Pendidikan di Indonesia dan Pendidikan di Malaysia - Putri Nelta, Sonya; Mislaini; Ashavira Julian Dias (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2024)
Education is one of the main factors in developing quality human resources. The education systems in Indonesia and Malaysia have unique characteristics that reflect the cultural, social values and national policies of each country. The education system in Indonesia and Malaysia has experienced significant development, driven by the need to create superior human resources capable of competing globally. In Indonesia, the transformation of the education system is marked by changes in curriculum policies, such as the Merdeka Curriculum, which aims to increase consistency and creativity in the learning process. The government also continues to encourage equal access to education in all regions and strengthen the character of education. Meanwhile, Malaysia is focusing its development on technology-based and vocational education through the implementation of the STEM (Science, Technology, Engineering, and Mathematics) curriculum and the Technical and Vocational Education (TVET) program. Both countries face their own challenges in implementing equitable and sustainable education policies, but both continue to innovate in order to improve the quality of education. This journal compares the development of the education systems in Indonesia and Malaysia, including policies, structures and challenges faced in efforts to improve the quality of education.